Contribution of Non-Wood Forest Products to Community Income Around Mount Bromo Forest Areas with Special Purposes - Agustina, Ana; Wardana, Miki Satria; Rahmadwiati, Rissa (Universitas Panji Sakti, 2024)
. Utilization of Non-Wood Forest Products (NWFP) by the community is divided into three categories according to economic value, namely the level of subsistence, the level of local use, and commercial. The interaction of the surrounding community with KHDTK Mount Bromo includes various uses of the area in the form of wood and non-wood, including NWFPs. Therefore, it is necessary to study the contribution of NWFPs to the income of the people around KHDTK Mount Bromo. This study aims to assess the potential of Non-Wood Forest Products (NWFPs) in the vicinity of KHDTK Mount Bromo and determine their contribution to the local community's income. This study was conducted from January to March 2023, this study used an interview method with a questionnaire to obtain information from respondents chosen by purposive sampling in Delingan Village, Gedong Village, and Sewurejo Village, Karanganyar Regency, Central Java. The results of this study obtained information that the contribution of NWFPs to the income of the community around KHDTK Mount Bromo was 17.3% in Delingan Village, 5.18% in Gedong Village, and 20% in Sewurejo Village with the largest potential for NWFPs in the three research locations were durian, with an annual yield in Delingan Village of 1,040 kg, Gedong Village of 415 kg, and Sewurejo Village of 1,625 kg. The contribution of NWFPs in rupiah in Delingan Village is IDR 95,815,000/year; in Gedong Village is IDR 54,100,000/year; and in Sewurejo Village is IDR 116,490,000/year. The results of the F-test showed significant results with factors such as the age of the respondent, number of family members, education, land area, and distance from house to land on NWFP's income.